The Impact of Digital Learning Tools on Students’ Critical Thinking Development - Nur, Jumaidi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of educational technology has brought significant changes in the learning process, especially in encouraging critical thinking skills as one of the main competencies of the 21st century. This study aims to analyze the influence of the use of digital learning tools on the development of critical thinking skills of high school students in Kutai Kartanegara Regency, East Kalimantan. This study uses a quantitative approach with a quasi-experimental design involving 60 students in grade XI who are divided into two groups, namely the experimental group that learns using digital learning tools and the control group that learns using conventional methods. Data were collected through critical thinking skills tests before and after treatment (pre-test and post-test) and analyzed using a paired sample t-test to identify significant differences between groups. The results of the study show that the use of digital learning tools has a positive and significant effect on improving students' critical thinking skills. Interactive digital media has been proven to be effective in improving students' analytical skills, evaluation, and reflective reasoning during the learning process. This study concludes that the integration of digital technology in teaching and learning activities can strengthen the quality of learning while developing students' critical thinking skills. These findings provide practical implications for educators and curriculum developers in designing innovative technology-based learning strategies that align with the demands of modern education.